2023
DOI: 10.1039/d3ra00100h
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional fluorescent Eu-MOF probe for tetracycline antibiotics and dihydrogen phosphate sensing and visualizing latent fingerprints

Abstract: Water-stable Eu-MOF as a fluorescent probe for detecting tetracycline antibiotics and dihydrogen phosphate in real samples and visualization of latent fingerprints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…When the Zn-MOF and tetracycline coexist, a slight redshift was observed in the absorption peak compared to tetracycline alone, suggesting the interaction between the Zn-MOF and tetracycline. 38 After Eu 3+ was introduced into the Zn-MOF to form Eu@Zn-MOF, the Eu@Zn-MOF would have the possibility of both the Zn-MOF and Eu 3+ binding with tetracycline. When tetracycline was added to the solution of Eu@Zn-MOF, its absorption peak appeared at 393 nm, which showed an obvious redshift in comparison to the absorption spectra of tetracycline alone and Zn-MOF + tetracycline, suggesting that tetracycline interacted with both the Zn-MOF and Eu 3+ in Eu@Zn-MOF.…”
Section: Resultsmentioning
confidence: 99%
“…When the Zn-MOF and tetracycline coexist, a slight redshift was observed in the absorption peak compared to tetracycline alone, suggesting the interaction between the Zn-MOF and tetracycline. 38 After Eu 3+ was introduced into the Zn-MOF to form Eu@Zn-MOF, the Eu@Zn-MOF would have the possibility of both the Zn-MOF and Eu 3+ binding with tetracycline. When tetracycline was added to the solution of Eu@Zn-MOF, its absorption peak appeared at 393 nm, which showed an obvious redshift in comparison to the absorption spectra of tetracycline alone and Zn-MOF + tetracycline, suggesting that tetracycline interacted with both the Zn-MOF and Eu 3+ in Eu@Zn-MOF.…”
Section: Resultsmentioning
confidence: 99%
“…These biologically active antibiotics are the new environmental pollutants when used in high concentrations. [18][19][20][21] Most of the antibiotics are non-degradable and therefore persist in the ecology for a longer time, making them a serious pollutant. 21b Studies suggested, that due to continuous ingestion of certain antibiotics employed excessively during the treatment of COVID-19 across the world, the bacteria displayed resistance toward it.…”
Section: Introductionmentioning
confidence: 99%
“…30 A novel luminescent Cd II -based MOF with a low detection limit of 0.42 ppm for SA and multiple ions was designed and synthesized by Wu's groups, and shows good structural stability and recyclability. 31 In addition, an Eu-MOF as a dual functional fluorescent sensor has been designed and synthesized for detecting dihydrogen phosphate (H 2 PO 4 − ) by Wiwasuku et al 32 The Eu-MOF can resist the interference of various anions to sensitively and selectively detect H 2 PO 4 − , based on fluorescence quenching. The acid–base mixed-ligand strategy is a reasonable method to construct LMOFs.…”
Section: Introductionmentioning
confidence: 99%